Critical review based on the actor-network theory of Models of Public Communication of Science and Technology - Martínez-Sahagún, Daniel; Escudero-Nahón, Alexandro (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2018)
Models of Public Communication of Science and Technology have not fulfilled their objectives. The problem originated when they inherited the anthropocentric and essentialist meanings of modern theories of communication. This paper explores the evolution of these theories and performs a conceptual analysis and a critical review or them. Results have shown that the theoretical explanations are not adapting to the scenarios generated by the fourth industrial revolution. Given these scenarios, the actor-network theory allows to redefine these concepts to democratize communication through a new model that interconnects the science with the technology.